NAVIGATING PERFORMANCE: SURFING ON THE OCEAN (BIG FIVE) PERSONALITY TRAITS - Helena M. Pongoh; Zevania E. V Gessal; Deske W. Mandagi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This systematic literature review discovers the elaborate relationship between the Big Five personality traits—Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism—and performance in various domains. Many researchers verify that big five personality traits have significant impact on performance across different fields. The article synthesizes findings from diverse studies, providing a comprehensive overview of the role personality plays in shaping individual performance outcomes. In this article a methodical approach is used to review literature; especially the articles published between 2017 and 2023 were identified using Scopus and Google Scholar. A total of 26 peer-reviewed articles were carefully selected and analyzed. The result shows (1) the key findings regarding the relationship between big five personality traits and performance discovered antecedents and consequences, each big five personality traits have a unique influence on performance. For instance, Conscientiousness strongly linked to both academic and job performance due to its association with diligence and reliability. Extraversion being the most influential in job performance and all personality traits positively significant in team performance. (2) the implications from those findings indeed can give fruitful overview in understanding and predicting performance in various domains. Employers, educators, researchers and employees benefit from them.